Diversion from prosecution to social work in scotland: a snapshot of current patterns and an examination of practice in three CJAs - Bradford, Ben (Report, 2011)
This report was commissioned by the Scottish Government (the SG) as a result of concerns raised by the diversion working group of the Pre-Disposal Programme Implementation Board. The numbers of cases diverted from prosecution have fallen in recent years (2006 onwards) and it was felt there was a need to investigate this issue further. This report details a small-scale research study on the use of social work related diversion schemes by Procurators Fiscal in Scotland.